GIS and the Academic Library: A Survey of Libraries Offering GIS Services in Two Consortia. - Camila Gabaldón; John Repplinger (Issues in Science and Technology Librarianship)
This paper summarizes the results of a survey of academic libraries in two consortia (the Orbis Cascade Alliance and the Oberlin Group) to determine the extent of Geographic Information Systems (GIS) implementation and characteristics of libraries that had implemented these services. Of the 103 libraries surveyed, 31 had already implemented GIS services and an additional 15 were considering its implementation. There were significant differences in the implementation rate between public and private institutions. Average materials budget was also higher for those libraries that had implemented GIS than those that had not. [ABSTRACT FROM AUTHOR]